Inherited and Acquired Muscle Weakness: A Moving Target for Diagnostic Muscle Biopsy - Stenzel, Werner; Schoser, Benedikt (Neuropediatrics, 2017)
Inherited and acquired muscular weakness is caused by multiple conditions. While the inherited ones are mostly caused by mutations in genes coding for myopathic or neurogenic diseases, the acquired ones occur due to inflammatory, endocrine, or toxic etiologies. Precise diagnosis of a specific disease may be challenging and may require a multidisciplinary approach. What is the current place for a diagnostic biopsy of skeletal muscle? Diagnostic muscle biopsy lost in this context its first-tier place in the primary diagnostic workup for some diseases, but it is still mandatory for others. We here summarize conditions in which we believe a diagnostic sample is most relevant and mention those in which a biopsy may be secondary or can even be left out. We would like to stress that muscle biopsy nowadays has a new important place in description and definition of new diseases, for example, discovered by modern genetic approaches.
Keywords: congenital weakness; congenital myopathy; congenital dystrophy; infantile inflammatory myopathy; next-generation sequencing; muscle pathology